Insect-based organic waste management: a sustainable pathway to enhanced ecosystem services and food security - Ayompe, Lacour M.; Masso, Cargele; Epie, Wesner N.; Crook, Elizabeth D.; Egoh, Benis N. (Frontiers in Sustainability, 2025)
Insect-based organic waste management (IBOWM) is revolutionary for tackling organic waste disposal and fostering sustainable food production. This review examines the multifaceted benefits of IBOWM, including its capacity to reduce landfill waste, decrease greenhouse gas emissions, and improve soil health through the practical application of nutrient-rich insect frass. A major contribution of this study is developing a comprehensive framework that illustrates how insect farming enhances ecosystem services by bolstering biodiversity and optimizing nutrient cycling. Drawing on current research and diverse regional case studies, the paper highlights successful IBOWM implementations while also identifying major challenges such as regulatory barriers and public acceptance issues. The economic implications are also explored, with an emphasis on job creation and sustainable livelihoods, particularly in rural communities. Additionally, the review underscores the critical need for supportive policies and harmonized regulatory frameworks across regions. Finally, future research directions are outlined, stressing the importance of standardized regulations, thorough economic assessments, and targeted public education initiatives. By creating a supportive environment for IBOWM, stakeholders can significantly advance sustainable waste management, enhance food security, and promote overall ecological health, ultimately paving the way for a more sustainable future.